Flight-time method modified: Development of a novel and more accurate method for measuring vertical jump height using a smartphone application - Nishioka, T.; Yamaguchi, S.; Inami, T. (International Journal of Sports Physiology and Performance, 2025)
Purpose The flight-time method (FT) is used for measuring vertical jump height (JH) in the field because of its convenience; however, FT overestimates JH when the lower limb is flexed at landing. Herein, we proposed a new method (ie, flight-time method modified [FTM]) to address the problem of FT and evaluate its validity and reliability.